Symptoms of antenatal common mental disorders, preterm birth and low birthweight: a prospective cohort study in a semi‐rural district of Vietnam. Issue 6 (17th April 2013) - Niemi, Maria; Falkenberg, Torkel; Petzold, Max; Chuc, Nguyen Thi Kim; Patel, Vikram
Abstract Objectives To examine the association of low birthweight (LBW) and prematurity with clinically significant symptoms of antenatal common mental disorders (ACMDs) during the third trimester of pregnancy in a semi‐rural area in Vietnam. Methods Prospective community‐based cohort study. Severity of ACMD symptoms was assessed with the Edinburgh Depression Scale, low birthweight was defined as below 2500 g, and gestational age was estimated according to last menstrual period. Reproductive and socio‐demographic risk factors were measured as potential confounders of the association between ACMD and the outcomes. We conducted bivariate analyses of association between ACMD and the perinatal outcomes, employing chi‐square tests, crude odds ratios and 95% confidence intervals. Multiple logistic regression analysis was used to adjust for confounding. Findings We found a prevalence of clinically significant symptoms of ACMDs of 37.4%, which were significantly associated with preterm birth (adjusted OR 1.98, CI95% = 1.14–3.43) and low birthweight (adjusted OR 2.24, CI95% = 1.02–4.95). Among the examined risk factors for the outcome measures, only maternal age was found to be statistically significant for low birthweight and preterm birth. Conclusions This study confirms that clinically significant symptom levels of ACMD in Vietnam are associated with preterm birth and low birthweight. These findings highlight the importance of cost‐effective public health interventions for ACMD in Vietnam and further exploration of its physiological link with preterm birth and low birthweight.